Marketing Strategy and image of Starbucks with focus on the Czech Republic and Turkey - Sadıkoğlu, Aylin; Průša, Přemysl, 1980-; Blažková, Hana; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2023)
The thesis looked into marketing techniques and efforts done by the coffee shops. It deeply researched the specific marketing efforts like positioning, segmentation, targeting, sensory marketing and extended marketing mix. These shed light into how coffee shops are gaining and preserving their market presence. These information helped better understand and analyze the similarities and differences between the strategies of regular coffee shops and the coffee giant Starbucks. Starbucks and their strategies were looked in depth. With the self conducted survey, consumer behavior ad opinion related information was gathered ad it helped better to understand the image of Starbucks in the Czech Republic and Turkey. Analysis on the data and comments were made, and respective recommendations were provided. Overall, the thesis helped to better understand how the Starbucks Company is perceived in the Czech Republic and in Turkey and helped bring more light to the consumer behavior, and where improvements can be implemented in the company's marketing strategies.
Vedoucí práce: Přemysl Průša
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2023
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2023
Způsob přístupu: Internet
Keywords: international business [obor bakal. práce]; bakalářské práce; bachelor's theses